Surgical site infections in Neurosurgery - Tromp, Sean Andrew (Division of General Surgery, 2023)
Background Surgical site infection (SSI) is associated with a high morbidity and mortality. We sought to define the incidence of SSI at our institution and examine the risk factors for infection. Methods An observational, retrospective cross-sectional review of 676 patients older than 13 years old treated at Groote Schuur Hospital in 2019 yielded 842 neurosurgical operations. These were analysed individually to determine SSI rate as well as risk factors globally, and in pathology groups and wound classes. The SSI cases then had further review of microbiology, laboratory markers of infection, clinical, and outcome data. Results The overall incidence of SSI was 4,9% per patient. Of these 33 cases, the majority were deep infections (n=28). The incidence was similar across pathology groups, and scheduling status, but operations starting at night had increased risk of infection. Infected wounds had the highest risk for SSI (8,7%) with external ventricular drain (EVD) insertion carrying the highest risk in clean operations (6,5%). Age was a risk factor for superficial SSI, while operative time and cerebro-spinal fluid (CSF) leak were risk factors for deep infection. 36,4% of SSI cases were culture negative. C-reactive protein (CRP) and change in white cell count (WCC) predict deep infection, functional outcome, and hospital length of stay (LOS). The deep SSI group outcomes were 53,6% functionally impaired, and mortality was 21,4%. Conclusion The SSI rate of 4,9% compares well with previous studies. Advanced age, contaminated wounds, and EVD's are high risk for later infection. Operative time and CSF leak are potentially modifiable risk factors for SSI. CRP and change in WCC are useful markers for diagnosis and predicting outcome. 75% of deep SSI cases had a poor outcome.